Support for the Japanese national badminton team using match videos in preparation for the Rio de Janeiro Olympic Games - Hirano, K.; Iizuka, T.; Ugaya, M. (Sports Science in Elite Athlete Support, 2017)
This paper describes the support using match videos that was provided for the Japanese national badminton team in preparation for the 2016 Rio de Janeiro Olympic Games. In order to help coaches and players effectively strategize for their matches, we provided them with match videos and match analysis data. The purpose of the match analysis was categorized as follows: (1) to define the play tendencies of opponents, and (2) to evaluate the performances of Japanese players for further training. Additionally, match videos were provided to the coaches and players through video streaming technology so that they could easily access them anytime. We suggest that these support assisted the coaches and players in preparing for their matches, especially in the decision-making process of formulating strategies.